Survey of Kansas Cow-calf producers - Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1983)
Results of a 1982 survey were compared to a similar survey conducted 5 years earlier to determine if the acceptance of management practices had changed during that time period. The cow herd size was similar in both surveys but there was a 6% increase in crossbred cows and a substantial change in sire breed. The breeding season had been shortened to 110 days but was still too long. There was no apparent change in acceptance of semen testing or pregnancy check but 23% more producers were using a worming program. Fly control ear tags were not available in 1977-78 but 68% were using them in 1982 (69% used 1 tag per animal and 31% used 2) with a majority tagging both the cow and calf. Implanting had increased from 25% to 58%, with 95% of those using Ralgro and 43% re-implanting at least once. In 1977-78 a feeder calf price of 47.25 per cwt. was considered desirable; 65 per cwt. was the average response in 1982.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Fly control; Fly tags; Implants